2017
DOI: 10.3389/fmicb.2017.01344
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Staphylococcus aureus and Methicillin-Resistant S. aureus in Foods Confiscated in EU Borders

Abstract: The aim of the study was to evaluate the potential role of the illegal entry of food in UE in the Methicillin-resistant S. aureus (MRSA) spread. We studied the prevalence and characteristics of Staphylococcus aureus and MRSA isolated from foods of animal origin confiscated from passengers on flights from 45 non-EU countries from 2012 to 2015 by the Border Authorities at Bilbao International Airport (Spain) and Vienna International Airport (Austria), as well as foods from open markets close to EU land borders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 50 publications
4
34
4
1
Order By: Relevance
“…Owing to many limitations we were unable to study the genetic-relatedness of our isolates. However, many studies have reported the clonal spread of food-borne S. aureus isolates containing multienterotoxin genes (Aydin et al 2011;Rodr ıguez-L azaro et al 2017). Taken together, our findings highlight the emergence of enterotoxigenic S. aureus producing SE-like as reported by many studies describing the roles of both SE-like and classical SE in staphylococcal food poisoning (Bianchi et al 2013;Emilie et al 2018).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Owing to many limitations we were unable to study the genetic-relatedness of our isolates. However, many studies have reported the clonal spread of food-borne S. aureus isolates containing multienterotoxin genes (Aydin et al 2011;Rodr ıguez-L azaro et al 2017). Taken together, our findings highlight the emergence of enterotoxigenic S. aureus producing SE-like as reported by many studies describing the roles of both SE-like and classical SE in staphylococcal food poisoning (Bianchi et al 2013;Emilie et al 2018).…”
Section: Resultssupporting
confidence: 73%
“…; Rodríguez‐Lázaro et al . ). The staphylococcal enterotoxin D (SED) was previously reported as the most frequent toxin type, after SEA, in staphylococcal food poisoning in dairy products (Bianchi et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, most of these transmission pathways lack regularity, making it difficult to determine the origin of the MRSA clone, especially when clones have spread across the country. As a traceable vector, the food chain poses a significant risk for MRSA transmission across geographic regions, as it has been demonstrated by the illegal introduction and commerce of MRSA-contaminated food (Oniciuc et al, 2015;Rodriguez-Lazaro et al, 2017). Thus, the aim of this study was to characterize the evolutionary dynamic and transmission potential of MRSA through the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Although no strain of S. aureus was found to carry the mecA gene, the presence of MRSA strains has been detected in different foodstuffs including raw bovine milk and cheese (Normanno et al, 2007;Papadopoulos et al, 2018), meat products (de Boer et al, 2009;Rodríguez-Lázaro et al, 2017;Van Loo et al, 2007), and raw chicken meat (Kitai et al, 2005;Kwon et al, 2006). Therefore, the presence of MRSA and antibiotic resistant strains in food of animal origin should be systematically monitored to protect public health.…”
Section: Resultsmentioning
confidence: 99%